Evaluation of laboratory diagnosis for cutaneous tuberculosis - Ilhan Afsar; Fatma Sule Afsar (Wolters Kluwer Medknow Publications, 2016)
Background and Aim: Cutaneous tuberculosis (CTB) is still difficult to diagnose due to its varied clinical presentation and limitations of diagnostic methods. The aim of this study was to evaluate the results of diagnostic laboratory tests available for CTB. Materials and Methods: Twenty-six skin biopsy specimens belonging to clinically suspected cases of CTB were studied retrospectively. The specimens were divided into two portions, one part processed for histopathological evaluation and the other was used for microscopy and inoculation for the isolation of mycobacteria. Polymerase chain reaction (PCR) technique was applied to 14 of 26 specimens to detect Mycobacterium tuberculosis complex (MTBC) DNA. Results: Of the 26 biopsy specimens, 11 were confirmed as CTB by identification of MTBC in culture and/or histopathologic affirmation. Of these, four were lupus vulgaris, four were TB verrucosa cutis, one was scrofuloderma, one was primary inoculation TB, and one was periorifical CTB. Culture for mycobacteria was positive for five (45.45%) specimens, while histopathologic affirmation was obtained in ten (90.90%) specimens. Acid-fast Bacilli were not demonstrated in any of the specimens on microscopic examination. The PCR was found to be applied to six of the 11 specimens diagnosed as CTB and was positive in two specimens (33.3%), which were positive for growth in culture and histopathological correlation. Conclusion: The recovery rate of MTBC from biopsy specimens was found to be satisfactory for CTB with histopathological correlation, but the combination of culture with a rapid method, PCR, may improve the diagnostic rate.